Galpa : Short Stories by Women From Bangladesh - Azim, Firdous; Zaman, Niaz. (Dhaka : Rachana, Writers.ink, 2006)
A renowned Buddhist meditation teacher, born in Korea and educated in the United States, illuminates a path to inner peace and balance amid the overwhelming demands of everyday life by offering guideposts to well-being and happiness in eight areas.
Keywords: Conduct of life; Spiritual life--Buddhism.; Large type books